Proceedings of the 4th International Conference on Computer Engineering and Networks CENet2014 - Wong, W. Eric (Springer International Publishing, 2015)
This book aims to examine innovation in the fields of computer engineering and networking. The book covers important emerging topics in computer engineering and networking, and it will help researchers and engineers improve their knowledge of state-of-art in related areas. The book presents papers from the 4th International Conference on Computer Engineering and Networks (CENet2014) held July 19-20, 2014 in Shanghai, China.